Thermo- mechanical Coupling Analysis of Friction Plate of Wet Friction Clutch - Yang Yongqiang; Li Xiaoying; Cao Botao; Zhang Chunxia; Zhang Man (Jixie chuandong)
Based on the dynamics research of wet friction clutch,the engagement heat flux of friction clutch is calculated by friction power method,and the heat convection of wet friction clutch is discussed. The model of friction plate is established by using the finite element method,and the temperature field and the stress field of its are analyzed. The results of thermo- mechanical coupling field show the radial temperature of friction plate increase with the increase of radius,the thickness direction temperature is close to the surface region of friction plate. The circumferential tensile stress appears in the region close to the outer edge,while the circumferential pressure stress appears in the region close to the inner edge. The radial pressure stress is in the friction surface,and the radial tensile stress is in inner region of friction plate. The result provides the theoretical foundation for the thermal failure analysis of friction clutch.